2021
DOI: 10.1002/aur.2660
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between autism spectrum and sleep–wake traits

Abstract: Autistic children and adults often have sleep disturbances, which may affect their and their family's quality of life. Yet, the relationship between sleep-wake patterns and autism spectrum traits is understudied. Identifying such relationships could lead to future research elucidating common mechanistic underpinnings. Thus, we aimed to determine whether sleep-wake patterns, specifically related to sleep, physical activity, and the daily sleep-wake rhythm (i.e., circadian rhythm), are associated with autism spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 71 publications
(101 reference statements)
1
10
0
Order By: Relevance
“…In this study, we also report that a lower percentage of hours of nighttime sleep and lower stability of motor activity, sleep, and light exposure are associated with restrictive behavior, self-injurious behavior, somatic complaints, and withdrawal. Though no causal relationships can be drawn from our data, these results are in agreement with previous studies that found higher variability and a decreased strength of the circadian rhythm in those with more pronounced core autism spectrum traits (Elkhatib Smidt et al, 2021 ; Yavuz-Kodat et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we also report that a lower percentage of hours of nighttime sleep and lower stability of motor activity, sleep, and light exposure are associated with restrictive behavior, self-injurious behavior, somatic complaints, and withdrawal. Though no causal relationships can be drawn from our data, these results are in agreement with previous studies that found higher variability and a decreased strength of the circadian rhythm in those with more pronounced core autism spectrum traits (Elkhatib Smidt et al, 2021 ; Yavuz-Kodat et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Though most earlier research has relied on subjective data to measure sleep functioning, use of objective data has increased in recent years, with a number of papers including polysomnography or actigraphy to analyze the relationship between sleep and behavior difficulties in ASD (Aathira et al, 2017 ; Allik et al, 2006a ; Elia et al, 2000 ; Elkhatib Smidt et al, 2021 ; Fletcher et al, 2017 ; Gagnon et al, 2021 ; Goldman et al, 2009 ; Leader et al, 2022 ; Malow et al, 2006 ; Richdale et al, 2014 ; Yavuz-Kodat et al, 2020 ). New generation actigraphs such as Ambulatory Circadian Monitoring (ACM) devices offer valuable information about light, temperature and movement, allowing both sleep parameters and other circadian data to be collected in studies in autistic populations (Ballester et al, 2019 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To study the relationship between sleep and clinical symptoms and neurobehavioral traits, we selected assessments measuring traits and behaviors associated with sleep in other clinical populations including ASD and clinical high-risk for psychosis populations [ 13 , 14 , 44 46 ]. We tested if there was an effect of sleep on positive psychosis-risk symptoms, Autism-related behaviors, real-world executive function, and emotional or behavioral problems.…”
Section: Methodsmentioning
confidence: 99%
“…In a study of boys with ASD, sleep disturbance was found to moderate the relationship between ASD symptom severity and problem behaviors [ 13 ]. Sleep has also been shown to play a role in the executive functioning difficulties often observed in developmental psychiatric disorders [ 14 , 15 ]. For example, a recent cross-sectional study found sleep mediated the relationships between real-world executive function and both overall autistic traits and restrictive and repetitive behaviors [ 15 ].…”
Section: Introductionmentioning
confidence: 99%